Teknik Sniffing Jaringan Menggunakan Wireshark - Richo Muhhamad Farhan; Gregorius Hendita Artha Kusuma (Universitas Pancasila, 2023)
Computer network security factor is an absolute thing in building a network. Basically, the security system owned by the operating system is not enough to secure computer networks. Therefore, to get a computer network security, we need a tool that can detect the existence of an attack mechanism from the network. Where the purpose of this attack is to make the computer that accesses it unable to run normally on a computer network. Wireshark is software that can analyze computer network activity so that it can help detect imminent attacks so users don't have to worry about these attacks.